2021
DOI: 10.1371/journal.pone.0255534
|View full text |Cite
|
Sign up to set email alerts
|

Older adults with non-communicable chronic conditions and their health care access amid COVID-19 pandemic in Bangladesh: Findings from a cross-sectional study

Abstract: Background Burgeoning burden of non-communicable disease among older adults is one of the emerging public health problems. In the COVID-19 pandemic, health services in low- and middle-income countries, including Bangladesh, have been disrupted. This may have posed challenges for older adults with non-communicable chronic conditions in accessing essential health care services in the current pandemic. The present study aimed at exploring the challenges experienced by older Bangladeshi adults with non-communicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
3
33
3
4
Order By: Relevance
“…Access to COVID-related services Acute COVID services [5,11,12] Supplementary oxygen services [5] ICU services [13] Access to non-COVID related services Homecare [14][15][16] Tele health [17][18][19][20][21][22][23][24][25][26][27][28] Routine/Outpatient health care [16,21,24,27,[29][30][31] Oral healthcare [24] Mental healthcare [11,12,19,29,30,[32][33][34][35][36][37][38] Medications [20] Palliative care services [13,23,39] Chronic healthcare services [40,41] Other primary healthcare services [42] Literacy and education Digital literacy [19,22,…”
Section: Main Themes Sub-themes Referencesmentioning
confidence: 99%
“…Access to COVID-related services Acute COVID services [5,11,12] Supplementary oxygen services [5] ICU services [13] Access to non-COVID related services Homecare [14][15][16] Tele health [17][18][19][20][21][22][23][24][25][26][27][28] Routine/Outpatient health care [16,21,24,27,[29][30][31] Oral healthcare [24] Mental healthcare [11,12,19,29,30,[32][33][34][35][36][37][38] Medications [20] Palliative care services [13,23,39] Chronic healthcare services [40,41] Other primary healthcare services [42] Literacy and education Digital literacy [19,22,…”
Section: Main Themes Sub-themes Referencesmentioning
confidence: 99%
“…23 Previous studies from India, Bangladesh and Hong Kong have reported difficulty accessing healthcare and/ or obtaining medication during the pandemic. [24][25][26] Although the previous literature from Nepal has suggested disruptions in health services amidst the pandemic, 20 it is unknown from patients' perspectives how much difficulty they experienced accessing healthcare amidst the pandemic. Framing the current study within the principle of vertical health equity, we aim to assess the relationships between pre-existing conditions and challenges in obtaining routine healthcare and medications during the COVID-19 pandemic among older adults in eastern Nepal.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The lockdown massively affected the healthcare system and influenced the methods of healthcare delivery. Social distancing and lockdown resulted in a significant decrease in physical activity level, loss of follow-up appointments with physicians and physical therapists (PTs), and delay or cancelation of surgical procedures [ 2 ▪ , 3 ▪ , 4 ].…”
Section: Introductionmentioning
confidence: 99%